The multinomial option pricing model and its Brownian and poisson limits - Frank Milne; Dilip Madan; Hersh Shefrin (Queen's University, Department of Economics, 1990)
The Cox, Ross, and Rubinstein binomial model is generalized to the multinomial case. Limits are investigated and shown to yield the Black-Scholes formula in the case of continuous sample paths for a wide variety of complete market structures. In the discontinuous case a Merton-type formula is shown to result, provided jump probabilities are replaced by their corresponding Arrow-Debreu prices.
Keywords: 330; Termingeschäft; Capital Asset Pricing Model; Theorie